A dentin hypersensitivity treatment using highly stable photothermal conversion nanoparticles. (5th March 2021) - Gao, Heqi; Zhang, Lanrui; Lian, Xiaoli; Wang, Yue; Jiang, Shihui; Wang, Guanhua; Dai, Xiaohua; Zou, Huiru; Ding, Dan
Abstract : A type of photothermal biocompatible organic nanoparticles with a high PCE (40.6%) was developed and investigated, followed by the achievement of a significantly more effective phototheranostic dental hypersensitivity treatment combined with laser. Abstract : Most of the currently available commercial photothermal agents suffer from issues in terms of photothermal instability and low photothermal conversion efficiency (PCE), which indeed impair their practical applications in disease treatment. Herein, a type of biocompatible organic nanoparticles (namely NDTB NPs) for an effective photothermal treatment with a high PCE of 40.6% was developed, which showed far higher photothermal stability compared with that of the clinically used indocyanine green. In addition, NDTB NPs combined with laser are significantly more effective than only laser irradiation in phototheranostic dental hypersensitivity treatments. This study thus provides an insight into the development of advanced photothermal NPs for practical phototheranostic applications.